Resíduos sólidos e os impactos socioambientais no rio Cereja: subsídios para a gestão sustentável em Bragança-PA - SILVA FILHO, Claudio Padilha da (Universidade Federal do Pará, 2017)
The generation of municipal solid waste and its disposal is a worldwide problem. The growth of urban centers, the population explosion and environmental conflicts of humanity have been primarily responsible for human pressure on water resources in most cities. This study aims to evaluate the distribution and gravimetric composition of municipal solid waste (MSW) deposited on the river Cherry in the city of Bragança-PA. They were spread over 3.5 kilometers of urban stretch of the river 5 different points for collection of MSW during the rainy and dry season. The analysis of gravimetric composition of municipal solid waste was conducted a questionnaire on environmental awareness to people living around the river and the metrics of environmental integrity indicator (IIA) at the point of collection. The gravimetric composition of MSW in the rainy season was composed of rubber (37%), metal (23%), glass (13%) and paper / cardboard (9%). In the dry season, the highlights were polymerized / hard plastic (35%), metal (28%), polystyrene (19%). The IIA River Cherry presented classification of medium to low in relation to the diversity of habitats. Environmental characterization, the collection point showed better condition was point 1 (P1) and the collection point worse condition was P4. Gravimetric analysis of MSW disposed along the river showed a significant percentage of insusceptible material recycling. Note the need for environmental education program to promote actions that reduce and separate the MSW at the source, encouraging recycling, collection, processing and proper disposal.